The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1413-81232017229.13312017
|View full text |Cite
|
Sign up to set email alerts
|

Estupro e gravidez de meninas de até 13 anos no Brasil: características e implicações na saúde gestacional, parto e nascimento

Abstract: Sexual violence against children and adolescents is a serious threat to the rights and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
28

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 7 publications
1
10
0
28
Order By: Relevance
“…Adolescent pregnancy, unfortunately, is an expressive phenomenon in Brazil, with growing concern due to the number of records of live births involving mothers between 10 and 14 years old, a group of greatest gestational vulnerability, for both mother and baby. Among the analysis, this was seen when it was identified that 15.9% of births were premature, similar to other studies, which may be associated with lack of support in the monitoring of pregnancy, biological immaturity, fragility in the family structure, enhanced when associated with socioeconomic and geographic factors (4,(30)(31) .…”
Section: Discussionsupporting
confidence: 75%
“…Adolescent pregnancy, unfortunately, is an expressive phenomenon in Brazil, with growing concern due to the number of records of live births involving mothers between 10 and 14 years old, a group of greatest gestational vulnerability, for both mother and baby. Among the analysis, this was seen when it was identified that 15.9% of births were premature, similar to other studies, which may be associated with lack of support in the monitoring of pregnancy, biological immaturity, fragility in the family structure, enhanced when associated with socioeconomic and geographic factors (4,(30)(31) .…”
Section: Discussionsupporting
confidence: 75%
“…The studies' second main focus was teen pregnancy [29][30][31][32] , including socioeconomic profile 33 and social vulnerability 34 , paternal responsibility 35 , and rape-related pregnancies 36 . The experiences of pregnancy and abortion of the population of children, adolescents, and young people living on the street are also among the topics covered 37 , along with pregnancy and childbirth in prisons 38 .…”
Section: Thematic Lines and Sample/data Originmentioning
confidence: 99%
“…Todavia, de acordo com o Anuário Brasileiro de Segurança Pública, em 2015 foram registrados apenas 45.460 casos, sendo que deste valor 89% das vítimas eram do sexo feminino. Para o Instituto de Pesquisa Econômica Aplicada (Ipea), o número de violências sexuais ocorrido no país é de 527 mil/ano, sendo que apenas 10% destes casos chegam ao conhecimento das autoridades (FÓRUM BRASILEIRO DE SEGURANÇA PÚBLICA, 2016a;CERQUEIRA et al, 2017;ORGANIZAÇÃO MUNDIAL DA SAÚDE, 2013;SOUTO et al, 2017).…”
Section: Introductionunclassified
“…É inegável a forte relação entre abuso sexual e doença mental, as mulheres vítimas estão mais propensas a desenvolverem uma série de alterações psicológicas e cognitivas para o resto da vida, como: ansiedade, depressão, tendência ao suicídio, déficit dos processos cognitivos, culpa, vergonha, sensação de solidão e medo da morte (BORGES;DELL'AGIO, 2008;BRASIL, 2016b;CERQUEIRA et al, 2017;ORGANIZAÇÃO MUNDIAL DA SAÚDE, 2013;SOUTO et al, 2017).…”
Section: Introductionunclassified